The effectiveness of foster parenting programmed towards the betterment of english performance in SK Felda Selasih / Zulkifli Mohamed Hassan - Mohamed Hassan, Zulkifli (2002)
The task that 1 have completed is about Foster Parenting, which was done and completed at SK FELDA Selasih successfully. The foster parenting programmed was done with its aim was to upgrade the English Language proficiency in the school as whole and the students in Year 6 especially. Students from Year 6 were chosen and they are of different level of performance. There are some whom are so clever, and some just at the optimum level of understanding English. This done because it seems that the students are not fully involved in the usage of English outside their school hours. So, by doing this programmed it is to be my hope that the students can gain benefit and used the English among them. The programmed focused more to the grammar, and how to tackle questions in the UPSR Examination. Indirectly, they are also being exposed with daily communication, correct pronunciation and punctuation. It is my hope through this programmed there would be some more researchers to dig up students’ problem in mastering the English language and upgrade the findings written here.